3(3s+7)=75

Simple and best practice solution for 3(3s+7)=75 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3s+7)=75 equation:



3(3s+7)=75
We move all terms to the left:
3(3s+7)-(75)=0
We multiply parentheses
9s+21-75=0
We add all the numbers together, and all the variables
9s-54=0
We move all terms containing s to the left, all other terms to the right
9s=54
s=54/9
s=6

See similar equations:

| -2(x+5)+4x=0 | | 2x+10=30-6x | | x+2×40=102 | | 2x+10=-30-x6 | | ×-y=2,×+y=4 | | 26y=7 | | 4k+7=7k-;1;k=4 | | 4(2l+10)=48 | | (13n+1)=0 | | 6x12(-1)=72 | | 9x-(3x-9)=63 | | |13n+1|=0 | | x=0.6(300+700-0.7x) | | 2x2-–x=0 | | 4(3-5n)-7(5+n)+3=0 | | 3-4x=7x-1 | | 5x-12=3x+13 | | 16-4u=0 | | 5(x-3)=2(2x+6) | | 5(4x/3)=135 | | .06(n-450)=105 | | 70y-6=7 | | 5(11x-)=155 | | f(-3)=-3^2-5(-3)+36 | | 5(11x-)=-28 | | 5x-4=4x-10 | | 3x-11+5x/2=0 | | 6x-3=9x-24 | | 10x=-32-6 | | 7(4x+3)=27x+37 | | 6x-11-7=6(x-3) | | 3−7⋅3+4x=-18 |

Equations solver categories